(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Iatrogenic diseases are due to negligence or malpractice (Pezza et al.,2008). In human medicine, these conditions are widely described (Weingart et al., 2000), mostly for insurance issues related to hospitalization, while in veterinary medicine are reported only occasional case reports. 4155 clinical records related to cattle admitted to the Clinic for Ruminants and Swine of the University of Milan between 2005 and 2017 were analyzed. Clinical cases that required admission because of an iatrogenic related disease were selected for this study. For case selection, 3 experienced veterinarians examined the clinical records, cross-compared the selection and pick 114 cases (2,7%). The iatrogenic diseases were primarily caused by farmers (93%) than veterinary practitioner (7%). Iatrogenic diseases were caused mostly by erroneous administration of drugs (47,4%), excessive traction at birth (17,5%), improper milk or colostrum administration, frequently performed by oroesophageal tubing (16,7%) or by forced administration using a nipple bottle (12,3%). As verified by our study, farmers often performs medical, nursing and zootechnical procedures without adequate competences and sometimes choose medical treatment for sick animals without professional consultation of veterinarians.The veterinarian rule is fundamental in farmer education. Clinicians, especially in some professional branches as neonatology, should be more responsible of their assignments, avoiding delegation of specific procedures to unskilled staff. The importance of communication in improving management and health in dairy farms has been recently demonstrated (Jansen and Lam, 2012; Jansen et al., 2010). Effective communication has a key role in dairy herd health and communication strategies are required to support diseases control programs (Lievaart et al., 2008). More attention to iatrogenic issue may have a positive impact on animal and public health. Moreover, a decrease of unnecessary and injurious drug administration may result in a reduction of treatment costs and in prevention of antibiotic resistance.